THE INFLUENCE OF PRODUCT QUALITY , PRICE PERCEPTION AND BRAND IMAGE ON SATISFACTION AND CUSTOMER LOYALTY HOLCIM CONCRETE READYMIX IN JAKARTA - Budiastari, Sita (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2016)
The purpose of this research is to find a picture of the effect of product quality , price perception and brand image on satisfaction and customer loyalty ready mix concrete in Jakarta . This research is a quantitative study with descriptive and causal methods undertaken at Holcim Beton in 2013 with a sample of 100 customers in Jakarta and its surrounding the industrial and commercial segments project . Data collection by questionnaire respondents and analyzed using path analysis with SPSS version 20.0. The results of the study concluded that ( 1 ) product quality does not effect to customer satisfaction ( 2 ) Perception price positive and significant effect on customer satisfaction, ( 3 ) Brand Image does not have an influence on customer satisfaction, ( 4 ) all independent variables , quality of products , Perception price and a positive brand image and significant consequences for the dependent variable Customer satisfaction, with the value of determination of 50%, while 50% are influenced by other variables ( 5 ) Product Quality and significant effect on customer loyalty through customer satisfaction, ( 6 ) Perceived Price does not effect on loyalty through customer satisfaction, ( 7 ) brand image have effect and siginikan loyalty through customer satisfaction, ( 8 ) Dependent variable of product quality , price perception and brand image together and significant effect on customer loyalty through customer satisfaction, with value of determination of 77.4 %, and 22.6 % are influenced by other factors. The findings recommend that Holcim aims to improve product quality , perceived price and brand image to increase loyalty through customer satisfaction . It is also recommended to Holcim for increase of services and information to customers in order for increase customer satisfaction and loyalty. Keywords: quality of product, price perception, brand image, customer satisfaction, customer loyalty, ready mix concrete, Holcim in